EP946 Differences in correlation of progression-free survival and overall survival by clinical variables in epithelial ovarian cancer. (1st November 2019) - Paik, ES; Kang, M; Lee, JH; Kang, JH; Jeong, SY; Kim, MS; Lee, Y-Y; Kim, T-J; Lee, J-W; Kim, B-G; Bae, D-S; Seo, J; et al.
Abstract : Introduction/Background: To investigate significance of PFS as optimal surrogate endpoint for OS, and the differences in correlation of PFS and OS by different clinical variables in epithelial ovarian cancer (EOC) patients. Methodology: The clinical records of 1134 EOC patients treated at Samsung Medical Center between 2002 and 2015 were retrospectively reviewed. The primary outcome of this study was to evaluate the surrogacy of progression-free survival (PFS) for overall survival (OS) by clinical variables. Correlation analyses with all pair-wise comparison were performed to assess the association of PFS and OS for each clinical variable. After multivariate analysis for PFS and OS, scatter plot with hazard ratio (HR) (with 95% CI) of PFS and OS were drawn for clinical variables. Results: Of the 1134 EOC patients, 611 (53.9%) experienced relapse and a further 417 (36.8%) died within a median follow-up period of 47 months (range, 3–177 months). For entire cohort, there is a significant linear correlation between PFS and OS (p-value <0.0001), and the degree of correlation is high (Spearman correlation coefficient=0.8243). In Z-test using Fisher's transformation, patients with early stage (I, II) (0.9059, p<0.001), lower grade (0.9019, p<0.001), and non-serous histology (0.8853, p<0.001) showed higher correlation coefficient. In patients with no residual disease (0.8661, p<0.001), no pelvic lymph node metastasis (0.8275, p<0.001), no paraaortic lymph node metastasis (0.8267, p<0.001), higher correlation coefficient was shown. In scatter plot for HR of PFS and OS, presence of residual disease, high grade, neo-adjuvant chemotherapy, lymph node metastasis were not located within estimated regression area implicating low correlation coefficient. Conclusion: The treatment effect on OS is largely predictable according to that on PFS in EOC, especially for patients with early stage, low grade, non-serous, no residual disease, without lymph node metastasis. Disclosure: Nothing to disclose.